2000
DOI: 10.1590/s0101-20612000000300020
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in samples of "minas" cheese commercialized in the city of Belo Horizonte - Minas Gerais/Brazil

Abstract: or = 0.02ng/g) the mean contamination level of aflatoxin M1 was 0.08ng/g in fresh cheese, 0.36ng/g in canastra cheese and 0.62ng/g in standard cheese. No aflatoxin M1 maximum tolerance level in cheese has been established in Brazil.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
0
13
2
4
Order By: Relevance
“…However, the levels of AFM1 observed by Ardic et al (2009), Baskaya et al (2006), Dashti et al (2009), Fallah et al (2009, Gunsen (2002), Kamkar (2006), Prado et al (2000), Tekinsen and Tekinsen (2005), Tekinsen and Ucar (2008), Var and Kabak (2009) were significantly higher than those in the present study, ranging from 60% to 100% of the samples analyzed. Accordingly, Aygun, Essiz, Durmaz, Yarsan, and Altintas (2009) (Gurbuz, Nizamlioglu, Nizamlioglu, Dinc, & Dogruer, 1999;Kaniou-Grigoriadou, Eleftheriadou, Mouratidou, & Katikou, 2005;Taguchi, Fukushima, Sumumota, Yoshida, & Nishimune, 1995) who did not find AFM1 at detectable amounts.…”
Section: Number Of Samplescontrasting
confidence: 73%
“…However, the levels of AFM1 observed by Ardic et al (2009), Baskaya et al (2006), Dashti et al (2009), Fallah et al (2009, Gunsen (2002), Kamkar (2006), Prado et al (2000), Tekinsen and Tekinsen (2005), Tekinsen and Ucar (2008), Var and Kabak (2009) were significantly higher than those in the present study, ranging from 60% to 100% of the samples analyzed. Accordingly, Aygun, Essiz, Durmaz, Yarsan, and Altintas (2009) (Gurbuz, Nizamlioglu, Nizamlioglu, Dinc, & Dogruer, 1999;Kaniou-Grigoriadou, Eleftheriadou, Mouratidou, & Katikou, 2005;Taguchi, Fukushima, Sumumota, Yoshida, & Nishimune, 1995) who did not find AFM1 at detectable amounts.…”
Section: Number Of Samplescontrasting
confidence: 73%
“…As can be seen in Table 2, several researchers (Ardic et al, 2009;Elgerbi, Aidoo, Candlish, & Tester, 2004;Fallah, 2010a;Fallah, Jafari, Fallah, & Rahnama, 2009;Fallah, Rahnama, Jafari, & Saei-Dehkordi, 2011;Kamkar, 2006;Prado et al, 2000;Rahimi, Karim, & Shakerian, 2009;Seyrek, 2001;Tekinsen & Ucar, 2008) reported the occurrence of AFM 1 in various cheese types. The reported AFM 1 contamination levels vary from one study to another.…”
Section: Discussionmentioning
confidence: 95%
“…Devido a sua especificidade, o emprego de coluna de imunoafinidade atualmente está bem difundido em diferentes tipos de alimentos, como café, cerveja, leite, queijo, suco de maçã, iogurte e matrizes complexas como salsa e plantas medicinais. [20][21][22][23][24][25][26][27][28][29][30][31] O objetivo desse trabalho foi avaliar o grau de contaminação com aflatoxina B 1 em amostras de pimenta (Piper nigrum L.) e orégano (Origanum vulgare L.) comercializadas no estado de Minas Gerais. Inicialmente, foram avaliados alguns parâmetros de um método analítico, utilizando extração com metanol-água, purificação em coluna de imunoafinidade e detecção e quantificação da aflatoxina B 1 por cromatografia em camada delgada/densitometria.…”
Section: Introductionunclassified